The City as a Small Open Economy - John Hartwick (European Regional Science Association (ERSA), 2014)
We set out a small, open economy model of a city, one with local housing, government production and a non-traded good. We observe that a positive shift in labor productivity in the export sector generally results in a larger, higher-wage and more densely settled city. Production of the local public good increases for the special case of the public good 'counting' small in the utility function of the representative resident. Similar results obtain for the case of a city experiencing an exogenous improvement in a local climate amenity.
Keywords: R23; H40; F43; 330; small open city; urban public sector; law of urban growth